PENGARUH STRES KERJA TERHADAP KINERJA GURU SEKOLAH DASAR DI KECAMATAN TANGGUNGHARJO - Apremedian; Noor Miyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of job stress on the performance of primary school teachers in Tanggungharjo Sub-district. Job stress is one of the psychological factors that can affect the quality of performance, especially in the context of education. This study used the multiple correlation method involving 49 teachers as samples, which were selected using random sampling techniques with a margin of error of 5%. Data collection was conducted through a Likert scale-based questionnaire that had been tested for validity and reliability. The results showed that there is a very strong relationship between job stress and teacher performance, with a correlation value (R) of 0.977 and a coefficient of determination (R²) of 95.5%. The regression model used is significant, indicating that job stress has a significant negative effect on teacher performance. This finding suggests that any increase in job stress tends to decrease teacher performance. Therefore, it is important for schools and policy makers to design effective work stress management strategies, such as providing psychological support, creating a conducive work environment, and reducing excess workload, to improve teacher performance. This study makes an important contribution to efforts to improve the quality of basic education through managing teachers' work welfare.